Challenging the productivity mantra: academic writing with spirit in place. Issue 6 (19th September 2017) - Johnson, Laurel; Roitman, Sonia; Morgan, Ann; MacLeod, Jason
ABSTRACT: Academic writing groups aim to improve the quality and/or the rate of academic publications. In this article, the authors reflect on a writing group with academic and non-academic members that evolved over two years to uphold a deeper and arguably spiritual purpose. The group commenced with the aim of increasing its members' publication rates, but it developed to be a safe space for members to search for meaning as part of a fellowship of writers. This transition was based in the members' shared commitment to social justice values and individual concerns to generate meaningful research and writing experiences. The group's distinct processes, the shared values of its members and the site of the group meetings in a socially stigmatised community, all work to deepen its purpose beyond academic productivity. Though the group functions to strengthen individual and group norms that contribute to academic productivity, emergent norms and the fellowship of the writers foster a spiritual dimension in the group. This exploration of the spiritual dimension of a writing group adds to the long list of benefits of fellowship through academic writing groups.